The Influence of Sociodemographic Factors on Community Knowledge, Perceptions, Attitudes, and Practices towards COVID-19 Prevention Protocols : A Scoping Review - Lintang Puspita Prabarini; Kumboyono Kumboyono; Laily Yuliatun (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: WHO declared COVID-19 as a global pandemic due to its rapid spread and has beenconfirmed worldwide. Preventive efforts are made to minimize the virus spread among the community.Sociodemographicfactors play an integral role in determining the communityknowledge, perception,attitudes, and practice towards COVID-19 prevention protocols.Methods: This review was conducted on various journal articles to see the sociodemographic factors thatinfluence the levels of knowledge, perceptions, attitudes, and practices of the community towardsCOVID-19prevention protocols. Journal articles were selected under the PRISMA guidelines, from which 28 articleswere found to meet the predetermined criteria.Result: Several sociodemographic factors found to affect the levels of knowledge, attitudes, practices,and perceptions of respondents towards the COVID-19 prevention protocols were age, gender, education,marital status, occupation, socio economic status, area of residence, and nationality.Conclusion: Education and socio economic status/monthly income were found to be the main factors thatinfluenced the respondents’ level of knowledge. Individuals with higher education tended to take healthproblems more seriously, as shown by their better scores of compliance with the COVID-19 preventionprotocols, compared to the scores shown by other groups.